Upaya Guru Menggunakan Model Pembelajaran Aktif dalam Membangun Keaktifan Siswa Selama Pembelajaran Daring - Purba, Ruth Angeli Melki; Cendana, Wiputra; Pesik, Tobian Habel (Journal of Practice Learning and Educational Development, 2024)
During this pandemic, all educational institutions in Indonesia are required to implement the distance learning process. One such form is online learning, which is a learning process that relies on internet connectivity. In its application, online learning also still uses the 2013 curriculum, in which the learning process demands the active participation of students. However, observations show that there are problems in this aspect, namely the phenomenon of passive students. Active student participation is influenced by three factors, namely internal factors, external factors and teaching approach factors. In addressing this problem, the authors used the active learning model as one of the teaching approaches. The purpose of writing this final project is to explain the efforts of teachers using active learning models in building active student participation during online learning that are structured using descriptive qualitative research methods. In conclusion, through the application of this active learning model, teachers can help students in developing their abilities. The input of this journal is that in applying learning models, strategies, or methods, there should be enough attention paid to the internal factors that affect active student participation.